Unstable angina pectoris in a young male after first dose of COVID-19 MRNAvaccine - Billi Kinesya,; Makhyan Jibril Al-Farabi,; Yusuf Mannagalli,; Yudi Her Oktaviono, (Journal of the Pakistan Medical Association, 2024)
Some side effects regarding COVID-19 vaccination have been reported. The most common reports of cardiovascular issues were myocarditis and pericarditis. Although inflammation is the most common cause in this matter, there were only a few reports about ischaemic cases related to COVID-19 vaccines. These reports also commonly included older men who received a second dose of mRNA vaccination. We present a 25-year-old man with chest pain mimicking a heart attack after receiving the first dose of the mRNA COVID-19 vaccine. There were no known preceding cardiovascular risk factors. Workups were done, and the diagnosis made was unstable angina pectoris. This may remind physicians to increase awareness of cardiovascular side effects in this vaccination era, as it may be encountered even in younger patients. The patient was seen at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, in August 2022. Keywords: COVID-19 Vaccines, Myocarditis, RNA, Cardiovascular, Angina, Pericarditis.